Digital communication on higher education institutions: challenges and tools for research - Santos, Arlindo (2022)
Changes in the Higher Education (HE) paradigm in Portugal, have made the sector competitive where different Higher Education Institutions (HEI) adapt marketing strategies to foster their education offer and differentiation factors in order to attract and maintain a higher number of students. With the increasing reduction in birth rates in Portugal, the investment on internationalization becomes a need in order to maintain the number of students. At the same time, the rapid proliferation of communication technologies affected the recruitment of new students and the communication strategies of HEI. The Instituto Politécnico de Bragança (IPB), being aware of this reality and recognizing the importance of digital communication tools, established in its strategic plan 2018- 2022 objectives related to its internal and external communication in the digital context. For that purpose, various tools of research were conceptualized and implemented on an earlier phase of a digital communication plan. The originality and contribution of this work is to open this research methodology to the public sphere looking for critical analysis and construction.